Experimental Analysis on Mechanical Characteristics of Foundation Soil in Rift Valley Area of Kenya Nairobi-Malaba Railway - Hao, Bing; Zhou, Zhenghua; Li, Yuandong; Li, Xiaojun; Jin, Liguo (Frontiers in Earth Science, 2022)
The Rift Valley section of Kenya Nairobi-Malaba Railway locates in the Great Rift Valley of East Africa, with complex engineering geological conditions and well-developed geological structures. During the rainy season from March to May 2018, four large-scale ground fissures were formed in the first-stage project of the Nairobi-Malaba Railway of the valley floor section, accompanied by uneven surface settlement and trenches, seriously endangering the safety of the railway and its nearby projects. Through field investigation, it is preliminarily considered that the main reason induced ground fissures and surface settlement is the underlying soil layer being eroded by groundwater. The gully is further formed by surface water erosion on a base of uneven surface subsidence. The geological exploration trench at DK77 ground fissure revealed that the overlying soil layer is respectively grayish-yellow silty clay, cyan-gray volcanic ash, and brownish-yellow silty clay from top to bottom, and the underlying bedrock is volcanic tuff with wide cracks. The fluid flows out or into the bedrock through the cracks developing channels for groundwater up-down flowage. Under the erosion of groundwater to the underlying soil, this study proved the possibility of the occurrence of uneven settlement. When exposed to the groundwater, the underlying soil will exhibit special physical and mechanical properties which are conducive to the occurrence of ground cracks and subsidence. The conventional geotechnical tests are conducted for the three types of overlying soil, and the results reveal the causes of ground fissures and surface settlement from the physical and mechanical properties of the overlying soil and provide a basis for the further qualitative analysis of the mechanism of ground fissures and surface settlement.